Various torque tools calibration at NIM. (December 2021) - Meng, Feng; Jiao, Jing Pin; Zhang, Zhi Min; Zhang, Dian Long
Abstract: With the development of manufacturing industry, more and more torque tools are used in various industrial fields, such as torque wrench, torque multiplier, hydraulic torque wrench, electric torque wrench, various torque sensors, etc. The calibration of these tools is related to the quality of manufacturing products. National institute of metrology of China has established several torque standard devices and carried out calibration of various torque tools. This paper introduces the related work.